Pengenalan Landmark Pariwisata di Kulon Progo Berbasis Augmented Reality - ika arfiani; Murien Nugraheni; Muhammad Dzikrullah Suratin (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2023)
The tourism sector in Kulon Progo is showing a decline in terms of regional tourism development. The causative factor is the promotion that has not been able to maximize the availability of information technology. Several unmanaged tourist attractions such as Pringtali Temple, Lawangsih Cave and Kiskendo Cave. Disadvantages that make tourism objects less accessible to tourists include difficult access roads, uphill and steep terrain, damaged roads, and the lack of street lighting. Then an AR-based tourism introduction application was made. The method used is the Multimedia Development Lifecycle (MDLC) starting from the creation of the application concept, design, collection of materials, system implementation, and testing. This research produces an application based on Augmented Reality (AR) regarding the Introduction of Tourist Attractions in Kulon Progo which has been tested with an assessment percentage of 76.9%, which means the application is acceptable.